2014
DOI: 10.1166/jbn.2014.1917
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Therapy Using Nanomaterial-Mediated Thermolysis

Abstract: Nanomaterial-based systems present several novel therapeutic opportunities for cancer therapy based solely upon their unique physical and chemical properties. Despite advances in current cancer treatment, collateral damage to neighboring healthy tissues still cannot be avoided. By exploiting the strong optical and/or electromagnetic properties offered by nanomaterials, they are being employed as thermal nanoscalpels for the ablation of cancer cells. Through surface functionalization, these nanomaterials can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 170 publications
(227 reference statements)
0
8
0
Order By: Relevance
“…[1][2][3] This approach involves targeting magnetic nanoparticles to tumors and then inducing cytotoxic hyperthermia by applying an alternating magnetic field (AMF). Iron oxide nanoparticles are optimal for inducing hyperthermia, and their effectiveness as a cancer therapeutic should be evaluated according to the following criteria: 1) they should selectively target tumor cells, 2) they should easily penetrate tumor cells, 3) they should be internalized by tumor cells, 4) they should be biocompatible and nontoxic across a wide range of concentrations, 5) they should be easy to administer in the clinic, 6) they should be likely to be approved for clinical use, and 7) they should be targetable to specific tumor types or to organs with metastases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This approach involves targeting magnetic nanoparticles to tumors and then inducing cytotoxic hyperthermia by applying an alternating magnetic field (AMF). Iron oxide nanoparticles are optimal for inducing hyperthermia, and their effectiveness as a cancer therapeutic should be evaluated according to the following criteria: 1) they should selectively target tumor cells, 2) they should easily penetrate tumor cells, 3) they should be internalized by tumor cells, 4) they should be biocompatible and nontoxic across a wide range of concentrations, 5) they should be easy to administer in the clinic, 6) they should be likely to be approved for clinical use, and 7) they should be targetable to specific tumor types or to organs with metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Superparamagnetic iron oxide MNPs (magnetite, Fe 3 O 4 and maghemite, γ-Fe 2 O 3 ) have been used in numerous applications in biomedicine, such as magnetic resonance imaging (MRI) [ 6 ], drug delivery [ 7 ], and thermoablation therapy [ 8 ]. IONPs can be coated with hydrophilic layers followed by subsequent conjugation of target specific proteins (peptides, antigens and antibodies), which add much needed biocompatibility and target specificity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that using biodegradable polymeric and magnetic nanoparticles as gene delivery carriers could promote macrophage phagocytosis and activate CD8 + T cell reaction [15]. SPION is one of the most popular nano-carriers for gene delivery due to its high surface-to-volume ratio and specific magneticity [16][17][18]. In addition, the SPION-PEI had a low cytotoxicity [19].…”
Section: Discussionmentioning
confidence: 99%